Study of the Violence and Living Together in the Classrooms through a Questionnaire of Class Climate: The Provinces of Cordova and Granada - Inmaculada Aznar; Ma. Pilar Cáceres; Francisco Javier Hinojo (Universidad Autónoma de Madrid, 2018)
Nowadays in the majority of the educational institutions there exists an evident problem, the school violence. Numerous studies have showed information on the indexes of violence in the classrooms, which serve us as base to justify the need of an education for the living together in the school centers supported and reinforced by the joint work of the teachers who develop your educational labor in the above mentioned centers.   This work supposes an approximation to a reality educational that this very present in the classrooms of the top courses of the centers of Primary Education of the provinces of Cordova and Granada of the south of Spain. The aim(lens) of the study tries to form and analyze the situations of school conflict and the relations between(among) the student body to level of classroom, obtaining this way a general vision with regard to the topic of the conflict and school violence